The depsidones from usnea aciculifera - Vo, Thi Nga; Tuong, Lam Truong; Nguyen, Kim Phi Phung (Journal of Technical Education Science, 2016)
The lichen is an association between a fungus and a phytosynthetic symbiont, generally green algae or cyanobacteria. Lichens have a number of practical applications, especially as sources of medicinal substances. Usnea aciculifera Vain, a lichen growing widely and abundantly on the bark of Pinus dalatensis at Lam Dong Province, Vietnam, has not yet been chemically and pharmaceutically studied in Vietnam. Our chemical study on Usnea aciculifera lead to the isolation of three depsidones, including norstictic acid (1), stictic acid (2) and 8-O-methylstictic acid (3). Their chemical structures were elucidated by 1D and 2D NMR. Lichen substances such as depsides or depsidones are of interest as natural antibiotics. The presence of norstictic acid (1) and stictic acid (2) in high yield of around 0.13% and 0.15%, respectively; and possessing the ability in inhibiting cell growth of human colon adenocarcinoma HT-29 cells showed that this species seems to become a potential medicinal resource.